2017
DOI: 10.1140/epjc/s10052-017-4691-2
|View full text |Cite
|
Sign up to set email alerts
|

Warm modified Chaplygin gas shaft inflation

Abstract: In this paper, we examine the possible realization of a new inflation family called "shaft inflation" by assuming the modified Chaplygin gas model and a tachyon scalar field. We also consider the special form of the dissipative coefficientφ 2 and calculate the various inflationary parameters in the scenario of strong and weak dissipative regimes. In order to examine the behavior of inflationary parameters, the n s -φ, n s -r , and n s -α s planes (where n s , α s , r , and φ represent the spectral index, its r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
(65 reference statements)
2
3
0
Order By: Relevance
“…In Refs. [43,44], the authors have developed inflationary parameters by considering a shaft potential and a tachyon scalar field and found that their results are consistent with current observational data. Recently, Kobayashi and Seto [45] investigated the polynomial warm inflation and reported that their results are in consistence with BICEP2 and Planck data.…”
Section: Introductionsupporting
confidence: 58%
“…In Refs. [43,44], the authors have developed inflationary parameters by considering a shaft potential and a tachyon scalar field and found that their results are consistent with current observational data. Recently, Kobayashi and Seto [45] investigated the polynomial warm inflation and reported that their results are in consistence with BICEP2 and Planck data.…”
Section: Introductionsupporting
confidence: 58%
“…They studied the model for various types of Ω (dissipation parameter) and ξ (bulk parameter) and reported that the scalar spectral index (n s ) lies in the compatible range for less number of e-folds (N). The authors in [38] investigated the polynomial WI and confirmed the consistency of their results with recent astrophysical data. Sadjadi and Goodarzi [39] discussed oscillatory type of inflation with non-minimal kinetic coupling as a resolution of few number of e-folds ("non-minimal derivative coupling model [40]").…”
Section: Introductionsupporting
confidence: 63%
“…We will choose m 10 18 GeV in our calculations. (See also [20] for a study of shaft inflaton potential in a warm inflation scenario. )…”
Section: Shaft Inflation In 4d Spacetimementioning
confidence: 99%